Effectiveness of Passive Ultrasonic Irrigation Protocols in Simulated Complex Root Canal Cavities - Plazza, Flavia A. [UNESP] (2023)
This study aimed to evaluate the effectiveness of different Passive Ultrasonic Irrigation (PUI) protocols on debris removal and exposure of dentinal tubules in simulated complex root canal cavities. Twenty single-rooted human mandibular premolars with simulated root canal cavities were filled with the debris and randomly divided into ten groups based on the final irrigation protocol: 1-positive control; 2-negative control; 3-conventional irrigation (CI) with 2.5% sodium hypochlorite (NaOCl); 4-CI with 17% ethylenediaminetetraacetic acid (EDTA) followed by NaOCl; 5-three cycles of PUI for 20 s (NaOCl-NaOCl-NaOCl); 6-three cycles of PUI for 20 s (NaOCl-EDTA-NaOCl); 7-one 60 s PUI cycle (NaOCl); 8-one PUI 180 s cycle (NaOCl); 9-two cycles of PUI for 60 s (EDTA-NaOCl); and 10-two cycles of PUI for 60 s (NaOCl-EDTA). The groups were analyzed by SEM. The Kruskal-Wallis test was used at a 5% level. PUI showed a higher reduction of debris, similar to the positive control group (p > 0.05) and higher than the CI and negative control groups (p < 0.05). Regarding the exposure tubules, the CI groups were similar to the negative control group in all cavities (p > 0.05). The PUI groups were similar to the positive control group (p > 0.05). However, only groups 6, 7, and 10 were statistically different from the CI and negative control (p < 0.05). The protocols using PUI, comprising groups with three cycles of 20 s (NaOCl-EDTA-NaOCl), two cycles of 60 s (EDTA-NaOCl), or one cycle of 60 s (NaOCl), were more effective at removing debris and increasing the exposure of dentinal tubules.